1997
DOI: 10.1016/s0022-5347(01)68162-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Capsaicin as a Treatment for Refractory Detrusor Hyperreflexia: A Dual Center Study With Long-Term Followup

Abstract: Our study shows that repeated instillations of intravesical capsaicin are effective in treatment of patients with detrusor hyperreflexia due to spinal cord disease and that effectiveness of the treatment persists at least 3 to 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 26 publications
3
84
2
2
Order By: Relevance
“…However, we did not con®rm the good results obtained by other studies, 3 but this datum may be due to di erent drug concentration, vehicle, duration and frequency of treatment. Fowler et al reported an improvement of clinical and urodynamical parameters also in patients su ering from Multiple Sclerosis (MS) and neurogenic urinary incontinence.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However, we did not con®rm the good results obtained by other studies, 3 but this datum may be due to di erent drug concentration, vehicle, duration and frequency of treatment. Fowler et al reported an improvement of clinical and urodynamical parameters also in patients su ering from Multiple Sclerosis (MS) and neurogenic urinary incontinence.…”
Section: Discussioncontrasting
confidence: 94%
“…The clinical outcome of intravesical capsaicin, in patients su ering from refractory detrusor hyperre¯exia, has been recently reviewed by a dual-centre study with a long term follow-up. 3 De Ridder reported that the e ectiveness of the treatment persisted at least 3 ± 5 years. Such results have not been con®rmed by other American studies, perhaps because of di erent drug concentration, vehicle, duration and frequency of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, intravesical TRPV1 agonist (capsaicin and RTX) desensitization therapy is based on the concept that the C fiber-driven micturition reflex, which is inactive in the adult life, resumes control of micturition in both neurogenic and nonneurogenic cases of overactive bladder (reviewed in Szallasi and Fowler, 2002;Avelino and Cruz, 2006). In patients with neurogenic detrusor overactivity disorders, intravesical capsaicin (Lazzeri et al, 1996;De Ridder et al, 1997) or RTX (Cruz et al, 1997;Lazzeri et al, 2000;Kim et al, 2003;Silva et al, 2005Silva et al, , 2007 provides symptomatic relief by increasing bladder capacity and decreasing the number of daily incontinent episodes. In some patients, intravesical RTX even fully restores continence (Cruz et al, 1997).…”
Section: Transient Receptor Potential Channels As Therapeutic Targmentioning
confidence: 99%
“…70 Also, therapies that do not relieve obstruction yet affect visceral afferent nerves can be as effective for LUTS and abolishing unstable bladder contractions as those which relieve obstruction. 71 Evidence of neurogenic changes following BOO have also been observed in animal studies. In a study involving rats with urethral ligation, 20% of animals continued to have persistent hyperactive voiding after urethral deligation, even though their bladder weights had normalized.…”
Section: Comparative Ef®cacy Of the Current Agentsmentioning
confidence: 82%